Reduced Self-Awareness Following a Combined Polar and Paramedian Bilateral Thalamic Infarction. A Possible Relationship With SARS-CoV-2 Risk of Contagion? - Bartoli, Massimo; Palermo, Sara; Stanziano, Mario; Cipriani, Giuseppina E.; Leotta, Daniela; Valentini, Maria C.; Amanzio, Martina (Frontiers in Psychology, 2020)
Reduced self-awareness is a well-known phenomenon investigated in patients with vascular disease; however, its impact on neuropsychological functions remains to be clarified. Importantly, selective vascular lesions provide an opportunity to investigate the key neuropsychological features of reduced self-awareness in neurocognitive disorders. Because of its rarity, we present an unusual case of a woman affected by a combined polar and paramedian bilateral thalamic infarction. The patient underwent an extensive neuropsychological evaluation to assess cognitive, behavioral, and functional domains, with a focus on executive functions. She was assessed clinically in the acute phase and after 6 months from the stroke, both clinically and by magnetic resonance imaging. The patient developed a cognitive impairment, characterised by prevalent executive dysfunction associated with reduced self-awareness and mood changes, in terms of apathy and depression. Such condition persisted after 6 months. In May 2020, the patient underwent the serology test in chemiluminescence to detect IgG antibodies against SARS-CoV-2. The result of the quantitative test highlighted a high probability of previous contact with the virus. We suggest that reduced self-awareness related to executive dysfunction and behavioral changes may be due to combined polar and paramedian bilateral thalamic lesion. Metacognitive–executive dysfunction affecting the instrumental abilities of everyday life might make people less able to take appropriate precautions, facilitating the risk of SARS-CoV-2 contagion.